Sleep disorders and night-shift work in nursing students: a cross-sectional study - Belingheri, Michael; Luciani, Michela; Ausili, Davide; Paladino, Maria Emilia; Di Mauro, Stefania; De Vito, Giovanni; Riva, Michele Augusto (La Medicina del Lavoro, 2022)
Background: University students are known to have higher sleep disorders prevalence than the general population. Among them, nursing students are even more susceptible to sleep disorders. This study evaluates sleep disorders’ risk factors among nursing students and their potential association with symptoms and assesses whether night shifts affect sleep quality by increasing the prevalence of sleep disorders. Methods: A total of 202 nursing students were included; a self-administered questionnaire was used to collect data on sociodemographic and academic characteristics (i.e., gender, age, height, weight, and year of nursing program) and risk factors for sleep disorders (e.g., smoking, lack of physical activity, and coffee intake late in the evening). The survey included the General Health Questionnaire to assess perceived stress, the Sleep and Daytime Habits Questionnaire, and the Epworth Sleepiness Scale to assess sleep disorders symptoms. Results: A high level of perceived stress is associated with sleep disorders symptoms and with poor sleep quality. Daytime symptoms are also associated with smoking. Students who drink coffee late in the evening report fewer nighttime symptoms. Night shifts and their increasing number are not associated with sleep disorders symptoms. The perception of an unsatisfying academic performance is associated with daytime symptoms and poor sleep quality. Conclusions: Although night shifts seem to not affect sleep quality among nursing students, sleep disorders represent a critical issue in this population since sleep disorders symptoms may result in errors, accidents, or low academic performance.